Transplantation-free survival and interventions at 3 years in the single ventricle reconstruction trial - Newburger, Jane W; Sleeper, Lynn A; Frommelt, Peter C; Pearson, Gail D; Mahle, William T; Chen, Shan; Dunbar-Masterson, Carolyn; Mital, Seema; Williams, Ismee A; Ghanayem, Nancy S; Goldberg, Caren S; Jacobs, Jeffrey P; et al. (Circulation (New York, N.Y.), 2014)
In the Single Ventricle Reconstruction (SVR) trial, 1-year transplantation-free survival was better for the Norwood procedure with right ventricle-to-pulmonary artery shunt (RVPAS) compared with a modified Blalock-Taussig shunt (MBTS). At 3 years, we compared transplantation-free survival, echocardiographic right ventricular ejection fraction, and unplanned interventions in the treatment groups. Vital status and medical history were ascertained from annual medical records, death indexes, and phone interviews. The cohort included 549 patients randomized and treated in the SVR trial. Transplantation-free survival for the RVPAS versus MBTS groups did not differ at 3 years (67% versus 61%; P=0.15) or with all available follow-up of 4.8±1.1 years (log-rank P=0.14). Pre-Fontan right ventricular ejection fraction was lower in the RVPAS group than in the MBTS group (41.7±5.1% versus 44.7±6.0%; P=0.007), and right ventricular ejection fraction deteriorated in RVPAS (P=0.004) but not MBTS (P=0.40) subjects (pre-Fontan minus 14-month mean, -3.25±8.24% versus 0.99±8.80%; P=0.009). The RVPAS versus MBTS treatment effect had nonproportional hazards (P=0.004); the hazard ratio favored the RVPAS before 5 months (hazard ratio=0.63; 95% confidence interval, 0.45-0.88) but the MBTS beyond 1 year (hazard ratio=2.22; 95% confidence interval, 1.07-4.62). By 3 years, RVPAS subjects had a higher incidence of catheter interventions (P<0.001) with an increasing HR over time (P=0.005): <5 months, 1.14 (95% confidence interval, 0.81-1.60); from 5 months to 1 year, 1.94 (95% confidence interval, 1.02-3.69); and >1 year, 2.48 (95% confidence interval, 1.28-4.80). By 3 years, the Norwood procedure with RVPAS compared with MBTS was no longer associated with superior transplantation-free survival. Moreover, RVPAS subjects had slightly worse right ventricular ejection fraction and underwent more catheter interventions with increasing hazard ratio over time. http://www.clinicaltrials.gov. Unique identifier: NCT00115934.